DESAIN TEMPAT PENDIDIKAN TAHFIDZ AL QUR’AN LEMBAGA FIKRATUSSALAM II - Samsu Hendra Siwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
In Islam, the activity of teaching and learning the Quran is a deed that is glorified in the sight of Allah. Therefore, the growth of institutions engaged in the field of Quran education is fertile to educate the community so that they are not illiterate in the Quran. The Fikratussalam Educational Institution under the auspices of the Fikratussalam Foundation located in Pondok Pekayon Indah, South Bekasi, is engaged in the tahfidz Quran education and has around 520 students from adult and children's classes. The teaching system at this tahfidz Quran educational institution consists of 10 students each class with 1 teacher. This building (Fikratussalam II) is intended for child students. Classroom learning is only 2 hours per class. The obstacle faced by the partner, namely the Fikratussalam Foundation, is the creation of a design for the development of this Educational Institution in a new location that is in accordance with the needs of tahfidz Quran educational activities. The method of implementing PKM is carried out in the planning and then design steps, namely by initial measurement of the plot (site), then also in-depth interviews with the principal and head of the foundation and observations in the field. From this data, architectural design is then made. This design was then consulted with Mitra to get input, then followed up in the design. The result of PKM is an assistance in the architectural design drawing for the development of the Design of the Tahfidz Quran Education Place of the Fikratussalam II Institution (Jl. Ketapang Pondok Pekayon Indah, South Bekasi, Bekasi City). ABSTRAK Dalam agama Islam, kegiatan mengajarkan dan belajar al Quran merupakan sebuah amal yang dimuliakan di sisi Allah. Oleh karena itu, tumbuhnya lembaga yang bergerak dibidang pendidikan al Quran menjadi subur untuk mencerdaskan masyarakat agar tidak buta huruf al Quran. Lembaga Pendidikan Fikratussalam dibawah naungan Yayasan Fikratussalam yang berlokasi di Pondok Pekayon Indah, Bekasi Selatan bergerak di bidang pendidikan tahfidz Al Quran mempunyai murid sekitar 520 orang dari kelas dewasa dan anak-anak. Pada pembangunan gedung ini (Fikratussalam II) diperuntukkan bagi siswa anak-anak. Sistem pengajaran pada lembaga pendidikan tahfidz ini masing-masing kelas terdiri 10 murid dengan 1 guru. Pembelajaran di kelas hanya 2 jam tiap kelasnya. Kendala yang dihadapi mitra yaitu Yayasan Fikratussalam adalah pembuatan desain untuk pengembangan Lembaga Pendidikan ini di lokasi baru yang sesuai dengan kebutuhan kegiatan pendidikan tahfudz al Quran. Metoda pelaksanaan PKM yang dilakukan langkah perencanaan kemudian perancangan yaitu dengan pengukuran awal kavling (tapak), kemudian juga wawancara mendalam dengan kepala sekolah dan ketua yayasan serta pengamatan di lapangan. Dari data ini kemudian dibuatlah gambar perancangan (desain arsitekturnya). Desain ini kemudian dikonsultasikan pada Mitra untuk mendapatkan masukan, kemudian ditindaklanjuti dalam desain. Hasil PKM adalah bantuan gambar perancangan arsitektur pengembangan Desain Tempat Pendidikan Tahfidz al Qur’an Lembaga Fikratussalam II (Jl. Ketapang Pondok Pekayon Indah, Bekasi Selatan Kota Bekasi).